Heavy metals in drinking water and periodontitis: evidence from the national oral health survey from China - Shuduo Zhou; Wenjing Li; Jun Wan; Yixuan Fu; Hongye Lu; Na Li; Xu Zhang; Yan Si; Xing Wang; Xiping Feng; Baojun Tai; Deyu Hu; et al. (BMC, 2023)
Abstract Background Periodontitis has become an increasingly important public health issue, coupled with a high economic burden for prevention and treatment. Exposure to essential trace heavy metals has been associated with various diseases; however, the relationships between essential trace heavy metals and periodontitis remain inconclusive. Objectives To investigate the association between essential trace heavy metals in tap water and periodontitis in a nationally representative sample in China. Methods We conducted a nationwide study including 1348 participants from the Fourth National Oral Health Survey in the 2015-2016 period. The trace heavy metals concentration was measured in the local pipeline terminal tap water. Periodontitis was diagnosed according to the classification scheme proposed at the 2018 world workshop on the classification of periodontal and peri-implant diseases and conditions. We used weighted multivariable logistic regression to estimate the association between essential trace heavy metals and the risk of periodontitis. We additionally used spline analysis to explore the possible nonlinear dose-response associations. Results Periodontitis patients were exposed to higher concentrations of essential trace heavy metals. In adjusted models, for 1 SD increase in the concentration of iron, manganese, and copper in tap water, the risk of periodontitis increased by 30% (OR: 1.30, 95%CI: 1.12-1.50), 20% (OR: 1.20, 95%CI: 1.03-1.41), and 20% (OR: 1.20, 95%CI: 1.04-1.39), respectively. Stratified analyses demonstrated that the associations between essential trace heavy metals and periodontitis were higher in females, elders, and rural residents. Spline analysis revealed nonlinear exposure-response relationships between periodontitis and exposure to iron, manganese, and copper in tap water. Conclusions Exposures to essential trace heavy metals in drinking water were associated with greater odds of periodontitis. Given the growing burden of periodontitis, our study sheds light on tailored public health policies for improving drinking water standards to alleviate periodontitis impairment.